PENGARUH WORD OF MOUTH, PERSEPSI HARGA, LOKASI DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BU KETUT - Putu Pande Edy Swardinata; Estik Hari Prastiwi (Cahaya Ilmu Bangsa, 2024)
The aim of this research is to determine and analyze the influence of word of mouth, price perceptions, location and product diversity on purchasing decisions at the Bu Ketut store. The method for this research itself uses a quantitative method using multiple linear regression with the help of SPSS version 25 software as a tool for testing and analyzing data. The population taken in this research itself was buyers at the Bu Ketut Grocery Shop, totaling 96 people, then for the Accidental Sampling technique, and for the measurement scale using the Likert scale as the measurement scale. The results of the research itself show that based on the simultaneous test (f test) it proves that all independent variables, namely the variables Word of Mouth (X1), Price Perception (X2), Location (X3), Product Diversity (X4) together have a significant influence on the dependent variable is the purchasing decision (Y). The research results are based on partial analysis (t test) that all independent variables, namely the Word of Mouth variable (X1), Price Perception (X2), Location (X3), Product Diversity (X4) have a significant influence on the dependent variable, namely Purchase Decision (Y).